Learn From Home Using Youtube Platform in Teaching Competency Development Learning for Biology Education Students - Dwi Ratnasari; Mila Ermila Hendriyani (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2022)
This study aims to analyze the learn from home strategy during the Covid-19 pandemic using the Youtube Platform in teaching competency development for biology education students. The method used in this research is a descriptive method, using a questionnaire on student responses to the learning process. The sample used was Biology Education students, FKIP Untirta who took teaching competency development courses. The research was conducted when students were studying PKM courses at Sultan Ageng Tirtayasa University. The research instrument used was a questionnaire response to the learning process of Biology education students. The results of this study showed that learning to use the Youtube Platform when learning from home during the Covid-19 pandemic is an alternative that can be used in the learning process. As many as 82.10% of students feel that using Youtube provides effectiveness and efficiency in learning biology; 78.84% of students are very enthusiastic about using Youtube; and 76.70% of students feel that there is an attractiveness in being featured on Youtube as a distance learning medium. Keywords: Covid-19, Basic Teaching Skills, Learn From Home, Youtube